THE APPLICATION OF THE WAKALAH CONTRACT IN THE SALE AND PURCHASE OF LAND IN ACCORDANCE WITH ISLAMIC LAW: A STUDY IN TIRO SUB-DISTRICT, PIDIE DISTRICT, INDONESIA - Jamhuri Ungel; Tina Ramadhana (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2019)
Wakalah refers to the delegation of authority or power to another individual to execute a task in accordance with the power or authority granted by the grantor of the power of attorney. In addition to financing transactions involving the purchase and sale of real estate, wakalah is also a prevalent practise in the banking industry. Wakalah is a permissible practise in Islamic commerce for purchasing and selling due to its incorporation of the principle of mutual assistance. Furthermore, it is advisable for representations in purchasing and selling transactions to adhere to the principles outlined in the Al-Quran and Hadith, as recommended by Islam. The representative may receive compensation in the same way that he must abide by the muwakkil's directives when performing his duties. The muwakkil must be informed of any profits or gains that the representative may appropriate in accordance with the compensation stipulated in the agreement. Nevertheless, the land transaction in Lhok Igeuh village involved a wakalah in which a representative sold land without the muwakkil's knowledge at a price higher than the price set by the muwakkil. This study is informed by two inquiries: To begin with, what is the customary procedure for land purchase and sale involving representation or wakalah within the Lhok Igeuh village community? Furthermore, in the village of Lhok Igeuh, how does Islamic law perceive the application of wakalah in the purchase and sale of land? The findings of the study indicate that the implementation of wakalah/representation in Lhok Igeuh village contradicts Islamic law regarding representation. Specifically, the practise of representation by a representative exploits the sale of non-proprietary land; only the seller who sells his own property in its entirety is permitted to profit, not a representative or proxy. Representatives may only be remunerated commensurately. The wakalah practise of purchasing and selling land in the village of Lhok Igeuh, as prescribed by Islamic law, encompasses aspects of inequity and embodies the principles of deceit and reliability in the execution of representative responsibilities.